Índice de qualidade de água e déficit de oxigênio dissolvido como indicadores ambientais no monitoramento de microbacias - Campagnaro, Vanessa Fabiane (2009)
The physical, chemical and biological parameters that characterize water quality are submitted to several variations in time and space. Therefore, it is necessary a systematic monitoring to obtain a real valuation regarding the surface water quality variation. Due to the importance of maintenance and preservation of natural resources and considering that knowledge of geo-environmental characteristics and realities from a region is a keyinstrument for their sustainable development, this study evaluated the Water Quality Index of CETESB and deficit of dissolved oxygen (D), using them as environmental predictors in Cascavel River watershed, in the western region of Paraná State. Parameters of analysis such as thermotolerant coliforms, dissolved oxygen, pH, BOD5, total nitrogen, total phosphorus, temperature, turbidity and total solids were monitored at two sampling points, from June to December, 2008. The results accordance was evaluated according to the standards required for water Class II, based on Resolution No. 357 of CONAMA. For each collection occurrence, water quality index and deficit of dissolved oxygen were determined. Water quality was analyzed based on two methods and their compared results. During the monitoring, total nitrogen was the only variable that breaks the legal requirements concerning quality, since it showed concentrations above the limit established in 50% of collection occurrences at Point 1 and in 75% at Point 2. It was observed that water quality worsens as it gets close to the control section of watershed (P2), however, its average classification of quality was considered as 'good' for both collection points. The results show that WQI can be associated to D. This was registered when the values of WQI increased and the D ones decreased. The linear regression analysis between the two predictors showed a straight line with a regression coefficient (R2) equal to 0.91 with